2020
DOI: 10.3390/ani10111952
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Leptospira in Racehorses and Broodmares in New Zealand

Abstract: A cross-sectional survey was conducted to determine the seroprevalence of Leptospira in a cohort of horses and to evaluate potential risk factors for Leptospira seropositivity in horses in New Zealand. The convenience sample included 499 Thoroughbred racing and breeding horses from 25 commercial properties in North Island, New Zealand. A questionnaire was used to collect demographic data on horses and property-level information on grazing and management practices, pest (rodent) management, access to natural wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…The seroprevalence in Arabians (33.2%) is generally consistent with previous studies on mixed populations of healthy horses in northern Poland, indicating 20% [18] and 39.0% [17]. However, a much earlier study indicated seroprevalence as low as approximately 11% in healthy horses but much higher (up to 75%) when related to leptospirosis outbreaks on farms [19], which is consistent with studies from other countries [21][22][23].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The seroprevalence in Arabians (33.2%) is generally consistent with previous studies on mixed populations of healthy horses in northern Poland, indicating 20% [18] and 39.0% [17]. However, a much earlier study indicated seroprevalence as low as approximately 11% in healthy horses but much higher (up to 75%) when related to leptospirosis outbreaks on farms [19], which is consistent with studies from other countries [21][22][23].…”
Section: Discussionsupporting
confidence: 89%
“…Sometimes, according to local regulations, other cutoffs are used. For example in Croatia a titer of >400 is considered positive with exception of serovars Bratislava and Australis, when >200 is a positive cutoff [24], while in the latest study from New Zealand the end point titer was recorded at the highest dilution where at least 50% agglutination occurred and it mostly was 1:25 or 1:50 [23]. In this study, the cutoff 1:100 was used to make the data consistent with OIE manual recommendations and to make them comparable with the last study from Poland [17].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of horses that had anti-Leptospira antibodies in serum using MAT was 1.5% in one study [44], but up to over 80% in other studies [6,53,57]. In numerous other studies, the frequency of seropositive horses is in between [43,46,48,58]. Using a specific ELISA test for detecting anti-Leptospira antibodies, even in up to 98% positive-reacting sera, has been detected in horses affected with ERU [63].…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, where the history is suggestive of ERU but the ophthalmologic findings are questionable, the indication for vitrectomy cannot be reliably established by ophthalmologic examination. Examination of serum by micro agglutination test (MAT) unfortunately does not allow a reliable statement about a local leptospiral infection in the eye, because too many healthy horses in Europe [5,6,10,[41][42][43][44][45][46][47][48] as well as in other parts of the world [24,27,[49][50][51][52][53][54][55][56][57][58][59][60][61] have agglutinating antibodies in the serum.…”
Section: Introductionmentioning
confidence: 99%
“…São escassos os estudos soroepidemiológicos avaliando a soroprevalência de L. interrogans em cavalos de corrida (Hamound et al, 2011;Hamound et al, 2012;Bolwell et al, 2020). Estudos realizados no Jockey Club Brasileiro, localizado no Rio de Janeiro, demonstraram títulos reativos em 58,3% (Hamound et al, 2011) e 71,4% (Hamound et al, 2012 dos animais.…”
Section: Discussionunclassified